EXCHANGE IN MATILDA FILM BY ROALD DAHL BASED ON PETER BLAU’S PERSPECTIVE - Umar, Nur Hasaniyah; Mazaya, Nur Widad (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
People tend to gather with people who have the same orientation and can help to fulfill the needs and desires of each. This difference causes variations in behavior among people. In social life, variations in the behavior of each individual are often found, although sometimes they have similarities in opinion. Differences in people's behavior are also influenced by several factors such as specific goals, economic background, social strata, etc. These differences in behavior underlie the birth of social exchange theory based on Peter M. Blau’s perspective. This research is included as descriptive-qualitative research. The data sources that the researcher used in this study are primary data sources in the form of Matilda film by Roald Dahl and secondary data sources in the form of several literature related to the theory of literary sociology, social exchange, and social interaction. The researcher collects data sources through listening, watching, and note-taking techniques. Based on the theory applied to see the phenomenon of social exchange in the film Matilda by Roald Dahl. The results of this study indicate that there are several forms of social exchange in the film.